Evaluation of the influence of Chloride Sodium rape on the external application on the structural and functional condition of rats kidney on development - Gushcha, S.; Nasibullin, B.; Zukow, W.; Savitskyi, I.; Volyanska, V. (Journal of Education, Health and Sport, 2019)
Much attention has been paid to the study of the numerous effects of chronic stress and the methods of their correction, but some questions remain unanswered. Goal. To investigate the effect of highly mineralized sodium chloride mineral water (brine) on the structural and functional state of rat kidneys with experimental distress. White female rats weighing 180 - 220 g were ranked into three groups: group I intact rats (control), group II rats with a distress model (duration 30 days); group III - rats with a model of distress, who from 15 to 30 day of experiment received a course of external procedures with rapes. In group II rats, the development of distress caused dystrophic changes in the kidneys, which led to inhibition of their urinary, ion-regulating and excretory functions. To correct the manifestations of distress rats received a course of external procedures with brine (5 procedures for 2 hours a day). Renal function restored: GFR exceeds group I data by 30%, resulting in complete recovery of the diuresis. Urea excretion is restored, and creatinine excretion exceeds the control level by 30% (p <0.001). The concentration of potassium ions is restored to the control level, their excretion is reduced by 20%, and the urinary excretion of sodium and chloride ions is increased by — 90% and 57%. Microscopically — the structure of nephrons and their components without visual changes, that is, does not differ from the first group of rats. Conclusions. Studies have shown that with transdermal administration of sodium chloride brine has a significant protective effect on the course of pathological changes in the function of the kidney of rats against the background of the development of distress.